ENHANCING ELEMENTARY STUDENTS’ READING LITERACY THROUGH ARTIFICIAL INTELLIGENCE-BASED LEARNING MEDIA - Anri Ahmadi Harahap; Abrizal Hasibuan; Anita Adinda (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to investigate the integration of Artificial Intelligence (AI)-based learning media to enhance reading literacy among elementary school students. Using a descriptive qualitative approach through case study and literature analysis, the research was conducted at SDN No. 100311 Palsabolas, involving teachers and students who utilized adaptive reading applications, text-to-speech tools, and intelligent learning platforms. Data were collected through observation, semi-structured interviews, and document analysis, and validated by triangulation techniques. The findings reveal that AI-assisted media significantly improve students’ reading motivation, comprehension, and fluency. Quantitative comparison between pretest and posttest results showed notable progress, with the average literacy score increasing by 16–27 points across different indicators. Students demonstrated greater engagement and independence, while teachers benefited from automated performance analytics and personalized feedback tools. However, challenges emerged related to device limitations, technical competence, and overreliance on automated features. The study concludes that AI-based learning media serve not only as technological tools but also as pedagogical instruments that personalize instruction, foster digital literacy, and transform reading classrooms into more adaptive, interactive, and student-centered environments.